Integration of East Manggarai Leles Cultural Character Values in Mindful Learning as a Strategy to Develop Collaboration of Elementary School Students - Cornelia Amanda Naitili; Amirulah Datuk; Femberianus Sunario Tanggur (STKIP Taman Siswa Bima, 2025)
The development of digital technology and artificial intelligence (AI) has had a major impact on the world of education, one of which is the weakening of social interaction and the decline in students' collaboration skills due to the increasing tendency of digital individualism. This study aims to explore and analyze the integration of East Manggarai Leles cultural values through mindful learning approach as a strategy to develop collaboration skills of elementary school students. The approach used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, documentation, and literature study. The data were analyzed thematically to find patterns of meaning in learning practices that combine local cultural values with a mindful approach. The results show that the integration of cultural values such as emi lime (selfless help), responsibility, and trust in the learning process can create an inclusive and collaborative classroom atmosphere. Learning becomes more meaningful because students not only learn cognitively, but also socially and emotionally. The mindful learning approach allows students to be fully present in the learning process and build empathy towards others, which in turn improves their collaborative skills. This research confirms that the combination of local wisdom values and awareness-oriented learning approaches can be an innovative solution in shaping student character in accordance with the needs of 21st century education.